Determination of discharge capacity of rectangular side weirs using Schmidt approach - Emiroglu, M. Emin; Ikinciogullari, Erdinc (Elsevier Sci Ltd, 2016)
Side weir is a hydraulic structure placed parallel to channel axis or angled to the channel wall in order to divert flow from a channel. Classical De Marchi hypothesis has commonly been used in previous studies to estimate discharge capacity of side weirs. In the present study, the discharge capacity of rectangular side weir was investigated using the Schmidt approach. Competence of average nape height as considered by Schmidt was examined via supplementary laboratory tests. 843 experimental runs were used in the study. In addition, to determine the reliability of the Schmidt approach for calculation of discharge capacity, obtained results were compared with De Marchi and Dominguez approaches. This study showed that Schmidt and Dominguez approaches had similar tendencies for coefficient of discharge, but the scatter data in the De Marchi approach was more significant. It is obvious that Schmidt approach was quite reliable for calculation of the discharge capacity. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Side weir; Discharge capacity; Schmidt approach; De Marchi approach; Dominguez approach; Discharge coefficient